Why Might a Videogame Developer Join a Union?. (December 2017) - Weststar, Johanna; Legault, Marie-Josée
This paper contributes to the union renewal literature by examining the union voting propensity of workers in the high-tech tertiary sector of videogame development toward different forms of unionization. We used exclusive data from a survey of videogame developers (VGD) working primarily in Anglo-Saxon countries. When looking at the factors related to voting propensity, our data indicated that the type of unionism matters and that industry/sectoral unionism is an increasingly salient model for project-based knowledge workers. This is an important policy dimension given that the legal structures and norms in Anglo-Saxon countries still tend to support decentralized enterprise-based unionism. It is also important for unions insofar as their organizing tactics remain geared toward a shop-by-shop approach or, at least, a localized geographical approach. Although additional work is required, our analyses lends support to the argument that high-commitment and high-involvement workplaces can engender a desire for collective representation and voice such as is offered through unionization. Whether this is because such workplaces step over a breaking-point line where the requirement for full alignment with employer goals becomes untenable and a source of discontent, whether this represents the existence of dual commitment where a representative agent like a union is seen as necessary to protect the work that people love, or whether there is a combination of these forces is not yet clear, but it is a critical area of future study for project-based knowledge workers.